Reports ...: v.1-11, 1862-1865; 1871-1878 (Printed at the Government central press, 1871)
1-2. 1862-63-64-65. - 3. 1871-72. - 4. 1871-72: Delhi; Agra. - 5. 1872-1873. - 6. Eastern Rajputana, 1871-72 ans 1872-73. - 7. Bundelkhand and Malwa, 1871-1872; Central provinces, 1873-74. - 8. Bengal provinces of Patna, Gaya, Mongir. - 9. Central provinces, 1873-74 and 1874-75. - 10. Bundelkhand and Malwa, 1874-75 and 1876-77. - 11. Gangetic provinces from Dabaon to Bihar, 1875-76 and 1877-78.